Retrospective analysis of 235 unselected patients with mantle cell lymphoma confirms prognostic relevance of Mantle Cell Lymphoma International Prognostic Index and Ki-67 in the era of rituximab: long-term data from the Czech Lymphoma Project Database. Issue 4 (April 2014) - Salek, David; Vesela, Pavla; Boudova, Ludmila; Janikova, Andrea; Klener, Pavel; Vokurka, Samuel; Jankovska, Milada; Pytlik, Robert; Belada, David; Pirnos, Jan; Moulis, Mojmir; Kodet, Roman; et al.
Abstract Although a prognostic model (MIPI, Mantle Cell Lymphoma International Prognostic Index) for patients with mantle cell lymphoma (MCL) has been established, its clinical significance for daily practice in the rituximab era remains controversial. Data of 235 unselected patients with MCL from the Czech Lymphoma Project Database were analyzed. MIPI, simplified MIPI (s-MIPI) and Ki-67 proliferation index were assessed for all patients and for a subgroup of 155 rituximab-treated (RT) patients. MIPI divided all patients into subgroups of low-risk (22%), intermediate-risk (29%) and high-risk (49%), with median overall survival 105.8 vs. 54.1 vs. 24.6 months, respectively (p < 0.001). s-MIPI revealed similar results. The validity of both indexes was confirmed in RT patients. We confirmed the Ki-67 index to be a powerful single prognostic factor for overall survival (64.4 vs. 20.1 months, p < 0.001) for all patients and for the RT subset. Our results confirm the clinical relevance of MIPI, s-MIPI and Ki-67 for risk stratification in MCL also in the rituximab era.